Caracterização citogenética de representantes de Asparagaceae s.l. com ênfase nas subfamílias Agavoideae Herb., Lomandroideae Thorne & Reveal e Nolinoideae Burnett - Neves, José Achilles de Lima (2014)
Asparagaceae s.l. it is cytologically characterized by the occurrence of bimodal karyotypes and evolution by polyploidy. This work aimed to analyze the karyotypic variability in representatives of three subfamilies of Asparagaceae and its taxonomic implications, using staining techniques with the fluorochromes CMA and DAPI, followed by fluorescent in situ hybridization (FISH) with 5S and 45S rDNA probes. All 14 analyzed species showed bimodal or slightly bimodal karyotypes, consisting of metacentric, submetacentric and/or acrocentric chromosomes. Chromosome numbers ranged from 2n = 38 in Cordyline fruticosa to 2n = ca. 180 in Agave decipiens. The mean chromosome size ranged from 0.38 µm in Furcraea foetida to 3.76 µm in Furcraea selloa. Of the eight analyzed species of the Agavoideae subfamily, five (Agave angustifolia, Furcraea foetida, F. gigantea, F. selloa and Yucca aloifolia) presented karyotypes formed by 60 chromosomes, 10 large (l) and 50 small to medium (s), all with interstitial CMA+ bands, with two to four 45S and 5S rDNA sites. Among the five analyzed species of the subfamily Nolinoideae, four presented 2n = 40 (8l + 32s) and one Sansevieria cylindrica 2n = 120 (24l + 96s), all with pericentromeric CMA+ bands and two 45S and 5S rDNA sites per diploid complement. The difficulties encountered in understanding the phylogenetic relationships between Agavoideae, Nolinoideae and Lomandroideae may be related to the fact that they partly share the same ancestral genome. As well as having independently undergone different alterations and rearrangements in their genomes. These two factors would be responsible for both the similarities and the differences, respectively. This can be perceptible at the morphological and genetic level, which makes the taxonomic delimitation of these groups difficult.